2014
DOI: 10.1002/celc.201402359
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Thin Hollow Carbon Nanospheres for Pseudocapacitive Sodium‐Ion Storage

Abstract: Ultra‐thin hollow carbon nanospheres (UTH‐CNs) are fabricated for use as anodes of asymmetric sodium ion pseudocapacitors. The ∼3 nm thick amorphous carbon walls obtained from regenerated silk proteins as a template exhibit a well‐defined porous structure suitable for reversible sodium‐ion storage. The UTH‐CNs show remarkable electrochemical activity with sodium via a pseudocapacitive reaction, delivering a large reversible capacity as well as superior rate performance for more than 1000 cycles. The pseudocapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 45 publications
2
46
2
Order By: Relevance
“…To better understand the storage mechanism and the excellent high‐rate performance of SGCN for SIBs, the CV curves under different scan rates range from 0.1 to 15 mV s −1 are collected and depicted in Figure a,b. Generally, the current obeys a function relationship with the voltage during the sweep (Equation ): i=aυbwhere both a and b are the parameters . The capacity contributions from the diffusion‐controlled intercalation process and surface‐induced capacitive process can be qualitatively analyzed by the b ‐value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand the storage mechanism and the excellent high‐rate performance of SGCN for SIBs, the CV curves under different scan rates range from 0.1 to 15 mV s −1 are collected and depicted in Figure a,b. Generally, the current obeys a function relationship with the voltage during the sweep (Equation ): i=aυbwhere both a and b are the parameters . The capacity contributions from the diffusion‐controlled intercalation process and surface‐induced capacitive process can be qualitatively analyzed by the b ‐value.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the capacitive behavior is directly proportional to the surface area, showing that carbon material with high surface area might be designed for fast SIBs from another aspect. Recently, ultrathin hollow carbon nanospheres with a surface area of 400 m 2 g −1 showed a specific capacity of 150 mAh g −1 at 1 A g −1 through the surface‐induced capacitive behavior . Furthermore, Zhang et al reported a modified graphene with an expanded interlayer space of 0.4 nm and high surface area of 601.7 m 2 g −1 , leading to high rate capability of about 130 mAh g −1 at 5 A g −1 .…”
Section: Introductionmentioning
confidence: 99%
“…S9, and Fig. Thus, GNP//FM-CNS pseudocapacitors displays outstanding energy density of 248 W kg -1 at a power density of 139 W kg -1 , exceeding the previous results of All-graphene-battery, 15 UTH-CNs//ACs 13 , Nb 2 O 5 /C//ACs, 33 TiO 2 -graphene//ACs, 34 13 , graphene//graphene (red squares) 15 , Nb 2 O 5 /C//ACs (wine circles) 33 , TiO 2graphene//ACs (blue circles) 34 and LiTi 5 O 12 //ACs (black circles) 35 . The asymmetric pseudocapacitors were assembled using the samples pre-cycled by the half cell configuration.…”
mentioning
confidence: 58%
“…
COMMUNICATION
This journal is

We report microporous carbon nanosheets containing numerous redox active heteroatoms fabricated from exfoliated waste coffee grounds by simple heating with KOH for pseudocapacitive charge storage. 1,13,14,15

The bio-inspired nanomaterials had unique characteristics, showing superior electrochemical performances as cathode for asymmetric pseudocapacitors.…”
mentioning
confidence: 99%
“…However, conventional supercapacitors are limited due to their low energy character. Thus, advanced electrode designs comprising high surface areas, well-defined pore structures, and nano-dimensional structures are required to yield supercapacitors with improved energy and power characteristics [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%